Etoposide targets 2A protease to inhibit enterovirus 71 replication - Qinqin Liang; Sai Shi; Qingjie Zhang; Yaxin Wang; Sheng Ye; Binghong Xu (Microbiology Spectrum)
ABSTRACT Enterovirus 71 (EV71) is a major pathogen that causes hand, foot, and mouth disease (HFMD) in infants and children. Notably, no clinically approved drugs specifically target EV71. The EV71 2A protease (2Apro), a cysteine protease produced by the virus, is essential for the virus’ replication and has a significant impact on the functioning of host cells. Thus, it presents a valuable target for the discovery of antiviral medications. In this study, based on the monomers and their derivatives in the Library of Traditional Chinese Medicine (TCM), we performed virtual screening and biological experiments. We identified a derivative of a traditional herbal monomer, Etoposide, commonly isolated from the roots and rhizomes of Podophyllum spp. Etoposide inhibited replication of EV71 A, B, C, and CVA16 viruses in a concentration-dependent manner in a variety of cell lines with minimal cytotoxicity. Furthermore, both molecular dynamics simulations and site-directed mutagenesis assays revealed that Etoposide inhibited the activity of the EV71 2A protease by mainly binding to two residues, Y89 and P107. The findings indicate that Etoposide serves as a promising inhibitor of the EV71 2Apro, demonstrating strong antiviral properties and positioning itself as a formidable candidate for clinical trials against EV71.IMPORTANCEWe first used a drug screening approach focused on monomeric compounds and their derivatives from traditional Chinese medicine to identify an EV71 2Apro inhibitor—Etoposide. We then performed biological experiments to validate that Etoposide suppresses the replication of the EV71 virus in a concentration-dependent manner with minimal cytotoxicity to various cell lines. Remarkably, it shows inhibitory activity against EV71 A, B, C, and CVA16, suggesting that Etoposide may be a potential broad-spectrum inhibitor. We revealed a novel mechanism that Etoposide inhibits EV71 proliferation by targeting 2Apro, and the interactions with Y89 and P107 are of great importance. The findings suggest that Etoposide serves as a promising inhibitor of EV71 2Apro, demonstrating significant antiviral properties. It stands out as a strong candidate for broad-spectrum applications in clinical research.